Obras abertas em quadrinhos: estratégias semióticas de abertura no campo da manualidade - Calvet, Lya Brasil (2024)
The comics code holds a complex and flexible structure. The manipulation of elements such as line, colour, style, panel, panel-to-panel movement, page layout, and speech bubbles, that can associate narrative and aesthetic purposes, sheds light upon the reflection about the possibilities of decodification by the reader. In order to explore and potentialize the possible meanings of a comic, this research inspires itself in Umberto Eco’s reflections on the open work, which analyse the ways certain artistic messages stimulate an interpreter to go through multiple interpretation paths. We propose a practical experimentation of the knowledge through poetic and investigative views and doings regarding comics that reach opening through handicrafts, the object-comics. The research aims the analysis of these artefacts and the subsequent production of an open work in the form of object-comic, which will require a collaboration based on physical handling. As a theoretical-methodological framework, Peirce’s semiotics sustains the notions of continuity of the signs, in which interpretative processes possess a cyclical and infinite nature. Semiotics consists both of an analytical tool, to comprehend the way by which comics produce opening, and a creative tool, to deliberately promote the continuous renewal of the comic by the user-creator.